Dealing with heterogeneity: An analysis of Spanish universities - Berbegal-Mirabent, Jasmina (2019)
Universities are highly dependent on regulatory frameworks, the geographical setting as well as on requirements for the creation of the different outputs they pursue. As a result, universities are heterogeneous organizations. This study analyses universities’ heterogeneity in Spain. By using a dataset from the Spanish higher education system, we model the objective function of universities and investigate which factors help explain universities’ performance, in terms of the three missions that they mostly perform (teaching, research and technology transfer). Also, a cluster analysis is performed to categorise Spanish universities. The findings contribute to better understand the different behaviours shown by universities. The findings underline the heterogeneity of Spanish universities: while some universities focus more on formation (teaching) goals, other universities excel at disseminating knowledge through different scientific outputs. The study concludes with a detailed inter- and intra- group analysis.